Simulating the Thermal Efficiency of Courtyard Houses: New Architectural Insights from the Warm and Humid Climate of Tiruchirappalli City, India - Gunasekaran, Rajaa; Priya, Radhakrishnan Shanthi (Architecture (Basel), 2025)
In various climate conditions, courtyards have a major impact on a building’s energy efficiency and thermal performance. The purpose of this study is to understand and analyze the environmental aspects of a courtyard in a particular area. The chosen region is Trichy, which has generally warm-humid climate. To understand environmental factors like thermal comfort, natural ventilation, natural lighting, and microclimate, cases from the region were chosen. The primary objective of this paper is to utilize computational fluid dynamics (CFD) to investigate how these environmental factors affect the courtyard in the stated location. The chosen case is stimulated using DesignBuilder software. The field investigation is the first step in the study, which is then followed by the model-making process and stimulation. This study investigates the impact of environmental parameters on courtyard efficiency, focusing on their response to environmental conditions. Through field investigation and modeling of chosen examples, the study reveals critical elements for courtyard design success, emphasizing the relevance of knowing these characteristics for effective courtyard planning in the region. The results are beneficial for analyzing the courtyard’s circumstances since they take into consideration the courtyard’s performance towards microclimate and influences on various courtyard components. Additionally, they offer a helpful coefficient factor for additional courtyard studies.